2018
DOI: 10.32328/turkjforsci.381899
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Landscaping in Istanbul Technical University

Abstract: Universities have significant impacts on the environment because of their huge consumption of energy and materials. In the recent years, the universities have been considered as a role model of environmental responsibility. Over the last decades, some leading universities could perform significant sustainability projects in which sustainable landscaping of the campuses seems more effective. Istanbul Technical University (ITU) could also implement a list of renovations and green activities including rainwater h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Results were also reached where the constant creep rate of the pure salt was about 7 times higher than that of the salt with intercalations, located under the same experimental conditions [15]. According to theoretical studies and based on rheological tests on salt, shear stress is generated at the interface between two rocks due to the difference in physical and mechanical properties and different deformation between pure salt and interlayers [1], [4], [18], [19]. As the creep time increases, the shear stress increases progressively.…”
Section: Overview Of the Rheological Behaviour Of Saltmentioning
confidence: 99%
See 1 more Smart Citation
“…Results were also reached where the constant creep rate of the pure salt was about 7 times higher than that of the salt with intercalations, located under the same experimental conditions [15]. According to theoretical studies and based on rheological tests on salt, shear stress is generated at the interface between two rocks due to the difference in physical and mechanical properties and different deformation between pure salt and interlayers [1], [4], [18], [19]. As the creep time increases, the shear stress increases progressively.…”
Section: Overview Of the Rheological Behaviour Of Saltmentioning
confidence: 99%
“…Salt is a typical crystalline material, and its creep behaviour under stress is basically a macroscopic reflection of the internal microstructural changes that take place. This means that, under the action of external conditions, important changes will occur in the microstructure of the salt, which can lead to variations in its mechanical properties [18], [19].…”
Section: Overview Of the Rheological Behaviour Of Saltmentioning
confidence: 99%
“…The existing vegetation on campus contributes to a university’s sustainability not only by landscaping (Liu et al , 2022) but also due to its role in diminishing the temperature by providing shade and reducing carbon emission (Lauder et al , 2015). It maintains healthy soil and cleaner air (Pouya and Pouya, 2018). Green areas within the campus constitute notable factors in increasing the university’s visibility and image (Speake et al , 2013).…”
Section: Hypotheses and Conceptual Model Developmentmentioning
confidence: 99%
“…A synthetic review by Marchioni and Bessiu indicated that the application of permeable pavements in urban areas is both practical and effective in reducing runoff volume and improving water quality [58]. The broad application of permeable pavements on the campus of Istanbul Technical University has resulted in improved stormwater management [59]. By using NbSs such as vine-covered trellises and green roofs, it is possible to reduce the heat-island effect.…”
Section: Nature-based Solutions and Using Gis-based Maps To Measure T...mentioning
confidence: 99%